Partisipasi Masyarakat Dalam Pembentukan Peraturan Desa Di Desa Oeletsala Kecamatan Taebenu Kabupaten Kupang - Donald Finit; Rafael Rape Tupen; Megi Octaviana Radji (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Oeletsala Village Regulation Number 3 of 2020 Oeletsala Village Revenue and Expenditure Budget for Fiscal Year 2020, Oeletsala Village Regulation Number 3 of 2021 Oeletsala Village Revenue and Expenditure Budget for Fiscal Year 2021, Oeletsala Village Regulation Number 02 of 2022 Oeletsala Village Medium-Term Development Plan (RPJM-DESA) for 2022-2027, Oeletsala Village Regulation Number 01 of 2022 Accountability Report on the Realization of the Oeletsala Village Revenue and Expenditure Budget for Fiscal Year 2021, Oeletsala Village Regulation Number 01 of 2023 Accountability Report on the Realization of the Oeletsala Village Revenue and Expenditure Budget for the 2022 Fiscal Year. This research is an empirical legal research based on events that occur in the field and research conducted directly. The sources of research data are primary data, secondary data and tertiary data. The analysis of legal materials uses analysis to test data from specific to general which is carried out in a juridical-qualitative manner and presented in a descriptive form. The results of the study show that: (1). Community participation is the active participation of community members as individuals, groups, or communities in joint decision-making, program planning and implementation, as well as the process of community development inside and outside the community. The basics of emotional awareness and responsibility. (2). internal obstacles to community participation in the formation of Oeletsala Village Regulations, related to low knowledge and education factors and community work factors that take up a lot of time, external community participation in the formation of Village Regulations, namely related to the role of the Oletsala Village government in building relationships with the community.